2013
DOI: 10.1016/j.ejmhg.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of sensory taste thresholds for phenylthiocarbamide (PTC) taste ability in North Indian Muslim populations

Abstract: The ability to taste Phenylthiocarbamide (PTC), a bitter organic compound has been described as a bimodal autosomal trait in both genetic and anthropological studies. This study is based on the ability of a person to taste PTC. The present study reports the threshold distribution of PTC taste sensitivity among some Muslim populations of North India, as till now no detailed information is available. A survey was conducted among healthy individuals within the age range of 10-45 years who were randomly selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
2
1
3
Order By: Relevance
“…The data on PTC taste ability is extensive and a considerable deal of research has been conducted worldwide. Previous studies found the percentage frequency of non-tasters for PTC taste ability in Indians is 33.62% [42] which corresponds to 34.375% and 32.26 % (phenotypic and genotypic analyses, respectively) in the current study. Our findings were almost identical to those of this research.…”
Section: Discussionsupporting
confidence: 62%
“…The data on PTC taste ability is extensive and a considerable deal of research has been conducted worldwide. Previous studies found the percentage frequency of non-tasters for PTC taste ability in Indians is 33.62% [42] which corresponds to 34.375% and 32.26 % (phenotypic and genotypic analyses, respectively) in the current study. Our findings were almost identical to those of this research.…”
Section: Discussionsupporting
confidence: 62%
“…It has been shown that distribution of PTC tasters and non-tasters in the populations is bimodal [40]. As for discussions and for comparative purposes it should be noted that despite the autosomal nature of the sensitivity to PTC there is a trend to the fact that some more tasters are found among females than among males in the world populations studied [41]; although in one of the studies it was shown that the average threshold of the sensitivity to PTC was slightly higher among females compared to males (the differences were not statistically significant) [42]. It can be assumed that males, phenotypic non-tasters, have adaptation to the substances with a bitter taste, with which they traditionally have more frequent contact (alcohol, tobacco) than females.…”
Section: Resultsmentioning
confidence: 99%
“…The gustatory stimulus was also presented on a very small area of the tip of the tongue for a very short time. Many previous studies reported that olfactory sensitivity is significantly higher in females than in males (Hummel, Kobal, Gudziol, & Mackay‐Sim, ; Koelega, ; Schienle & Schöpf, ), whereas multiple studies of gustatory sensitivity indicated no significant difference between females and males (Hong et al, ; Hussain, Shah, & Afzal, ; Kunka, Doty, & Settle, ), although one study (Tunsuriyawong, Bagla, & Doty, ) reported that gustatory sensitivity is slightly higher in females than in males. Moreover, regarding the methods of stimulus presentation used in this study, we knew empirically that males do not perceive olfactory or gustatory stimuli with the same probability as females, even though the males do not necessarily report experiencing subjective olfactory or gustatory disorders in daily life.…”
Section: Discussionmentioning
confidence: 97%